Budaya Organisasi, Disiplin Kerja Terhadap Produktivitas Kerja Dimediasi Motivasi Pegawai PDAM Unit Kertapati Palembang - Yusro Hakimah; Yun Suprani; Muhammad Said (UNIVED Press, 2023)
The results of this study can be concluded as follows: 1. Organizational Culture has an effect on employee motivation, 2. Discipline has an effect on motivation, 3. Organizational culture has an effect on Work Productivity, 4. Discipline has an effect on Work Productivity. 5. Motivation has an effect on Work Productivity. 6. Organizational Culture has an indirect effect on Motivation as a mediating variable with a P-Value value of 0.003 0.05, 7. Discipline has an indirect effect on Motivation as a mediating variable with a P-Value value of 0.013 0.05 . the value of R2 for the latent variable of motivation as a mediating variable is 0.894, which means that this value identifies that variations in employee discipline at PDAM Palembang can be explained by exogenous latent variables (organizational culture and discipline) of 89.4% while the remaining 10.6% is explained by other variables. and the R2 value for the latent variable of Work Productivity is 0.937, meaning that this value identifies that variations in Work Productivity can be explained by exogenous variables of 93.7% while the remaining 6.3% is explained by variables not included in the study.